Using Predictive Storybooks to Foster Backward Counting: An Explanatory Sequential Study in Indonesian Kindergartens - Widayati, Sri; Simatupang, Nurhenti Dorlina; Wiryanto, Wiryanto; Siswono, Tatag Eko Yuli; Blazic, Milena Mileva (FKIP Universitas Lampung, 2025)
Using Predictive Storybooks to Foster Backward Counting: An Explanatory Sequential Study in Indonesian Kindergartens. Objectives: This study aims to examine the effectiveness of the storybook